Study of Dangers Radioactive Indexes in Soil Selected From Archaeological Nippur ( Nepher ) City in Qadsiyah Governorate–Iraq - Mose Kadem, Aamer; Najy Hady, Heiyam; Abdulhussein Abbas, Qaissar (Al-Qadisiyah Journal of Pure Science, 2018)
Was account dangers radioactive indexes for (25) a sample taken deeply (15-30) cm of soil Nippur (Nepher) City archaeological in qadsiyah governorate after it has been measuring the effectiveness of radiation radionuclide (thorium , uranium238U, potassium ) by the detector gamma rays from Type Sodium iodide Na (Tl) (3 "× 3") were ranges of each of the radium equivalent ranging from (42.710) to (65.263) and an average of (59.220) and activity concentration index ranged from (0.348) to (0.542) and an average of (0.490) and either Internal hazard index ranged from (0.141) to (0.206) and an average of (0.187) and external hazard index ranging from (0.115) to (0.176) and an average of (0.160) units Bq.Kg-1 respectively, either values absorbed dose in the air ranged from (22.208) to (34.346) and an average of ( 31.102) unit nGy / h, while the internal annual effective dose values ​​were (0.654) to (1.011) and an average of (0.916) and annual effective dose was (0.163 ) to (0.253) and an average of (0.229) units mSv/y respectively. And the results were within the permissible limits and do not constitute a danger to humans (tourists and workers) in the region, as well as those who dwell near the area studied.